2015
DOI: 10.1016/j.bpj.2015.10.048
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Mechanical Causes of Microtubule Catastrophe and Aging

Abstract: Tubulin polymers, microtubules, can switch abruptly from the assembly to shortening. These infrequent transitions, termed "catastrophes", affect numerous cellular processes but the underlying mechanisms are elusive. We approached this complex stochastic system using advanced coarse-grained molecular dynamics modeling of tubulin-tubulin interactions. Unlike in previous simplified models of dynamic microtubules, the catastrophes in this model arise owing to fluctuations in the composition and conformation of a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
157
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(170 citation statements)
references
References 67 publications
10
157
1
2
Order By: Relevance
“…Interestingly, we also occasionally observed indications of protofilament blocking in control microtubules in the absence of any drugs, an effect that could contribute to naturally occurring catastrophes. Previous work has shown that the catastrophe frequency might reflect the accumulation of structural defects, such as plus-end tapering due to asynchronously growing protofilaments [1][2][3][4]. Strikingly, we found that the behavior of a pre-catastrophe microtubule tip in control microtubules is similar to the ones that are expected to lack protofilaments after Eribulin binding: in both cases the growth rate, the EB3 comet intensity and the straightness index were reduced.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…Interestingly, we also occasionally observed indications of protofilament blocking in control microtubules in the absence of any drugs, an effect that could contribute to naturally occurring catastrophes. Previous work has shown that the catastrophe frequency might reflect the accumulation of structural defects, such as plus-end tapering due to asynchronously growing protofilaments [1][2][3][4]. Strikingly, we found that the behavior of a pre-catastrophe microtubule tip in control microtubules is similar to the ones that are expected to lack protofilaments after Eribulin binding: in both cases the growth rate, the EB3 comet intensity and the straightness index were reduced.…”
Section: Discussionmentioning
confidence: 45%
“…Asynchronous elongation of individual protofilaments can potentially lead to an altered microtubule-end structure that promotes sudden depolymerization, termed catastrophe [1][2][3][4]. However, how the dynamics of individual protofilaments relates to overall growth persistence has remained unclear.…”
Section: Discussionmentioning
confidence: 98%
“…, 2002, 2005; Coombes et al. , 2013), and others (Zakharov et al. , 2015) all share some version of a cis -acting nucleotide.…”
Section: Introductionmentioning
confidence: 86%
“…ªÐÑÅAE ×ÎÖÍÕÖÂÙËË ÏÑÅÖÕ ÃÞÕß ÐÂÔÕÑÎßÍÑ ÄÇÎËÍË, ÚÕÑ ÒÑÎËÏÇÓ ÃÖAEÇÕ AEÂÉÇ ÖÍÑÓÂÚËÄÂÕßÔâ. ®ÑÉÇÕ ÃÞÕß, ÐÂÃÎáAEÂÇÏÞÇ ÍÂÕÂÔÕÓÑ×Þ Ë ÔÒÂÔÇÐËâ ì àÕÑ ÒÓÑÔÕÑ ÕÇ ÔÂÏÞÇ ÕÇÓÏÂÎß-ÐÞÇ ×ÎÖÍÕÖÂÙËË?¯Â ÓËÔÖÐÍÇ 3à ÒÓËÄÇAEÇÐÞ ÓÇÊÖÎßÕÂÕÞ ÓÂÔÚÈÕÂ Ä ÓÂÏÍÂØ ÑÒËÔÂÐÐÑÌ ÐËÉÇ ÏÑÎÇÍÖÎâÓÐÑ-AEËÐÂÏË-ÚÇÔÍÑÌ ÏÑAEÇÎË, ÖÚËÕÞÄÂáÜÇÌ ÕÇÓÏÂÎßÐÞÇ ×ÎÖÍÕÖÂÙËË [28]. ²ÂÔÔÏÑÕÓÇÐ ÔÎÖÚÂÌ, Ä ÍÑÕÑÓÑÏ ÕÖÃÖÎËÐÞ ÒÓËÔÑÇAEË-ÐâáÕÔâ Ë ÑÕÔÑÇAEËÐâáÕÔâ ÒÑÛÕÖÚÐÑ, ÍÂÍ ÒÓË ÒÑÎËÏÇÓË-ÊÂÙËË ÑAEÐÑÙÇÒÑÚÇÚÐÑÅÑ ÒÑÎËÏÇÓÂ.…”
Section: ¿íôòçóëïçðõâîßðþç Aeâððþç ñ Aeëðâïëúçôíëø ë ïçøâðëúçôíëø ôäñunclassified